The Effectiveness of Local Wisdom in Landslide Disaster Management (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Every community group, even when coping with landslides, has the skills and ways to cope with the environment for its survival. This understanding and approach is referred to as "wisdom to cope with local events" or is also simplified to "local wisdom." The coping mechanism is created and born of any case, experience, knowledge, understanding, and meaning of every event, phenomenon, hope and problem that arises around it. This system is passed down from generation to generation through the process of socialization and its application depends on the level of consistency of understanding and its effects in their lives. The purpose of this study was to explore and determine the effectiveness of social capital in the handling of landslides. The methodology used is qualitative descriptive. The findings showed that in coping with landslides, each area has distinct attitudes and trends, and it happens from generation to generation. Its implementation in each area depends on subjective and objective conditions.